Are sexual minority youth overrepresented in foster care, child welfare, and out-of-home placement? Findings from nationally representative data. (March 2019) - Fish, Jessica N.; Baams, Laura; Wojciak, Armeda Stevenson; Russell, Stephen T.
Abstract: Background: Preliminary evidence suggests that sexual minority (e.g. lesbian, gay, bisexual, and same-sex attracted) youth are overrepresented in child welfare services. Yet, no study to date has been able to test this hypothesis with national data. Objective: Using a two-study design, we test whether sexual minority youth are overrepresented in child welfare, foster care, and out-of-home placement using nationally representative data from the United States. Participants and setting: Study 1 data are from the National Longitudinal Study of Adolescent to Adult Health ( n = 14, 154; Mean age = 15.4). Study 2 data are from wave three of the National Survey of Child and Adolescent Well-Being II ( n = 1309; Mean age = 15.0). Methods: For Study 1, we use adjusted logistic regression models to test differences in lifetime foster care involvement between sexual minority and heterosexual youth. In Study 2, we calculate a Disproportionality Representation Index (DRI) – a ratio of sample prevalence relative to the general population – to estimate whether sexual minority youth were overrepresented in child welfare and out-of-home care. Results: Study 1 results indicate that sexual minority youth are nearly 2.5 times as likely as heterosexual youth to experience foster care placement ( aOR = 2.43, 95% CI 1.40, 4.21, p = .002). Results from Study 2 show that sexual minority youth were largely overrepresented in child welfare services (DRI = 1.95–2.48) and out-of-home placement (DRI = 3.69–4.68). Conclusions: Findings are the first to demonstrate sexual minority youth's overrepresentation in child welfare, foster care, and out-of-home placement using nationally representative data and emphasizes the need for focused research on sexual minority youth involved in the child welfare system.